1990
DOI: 10.1128/iai.58.2.471-479.1990
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphisms among uropathogenic Escherichia coli isolates: pap-related sequences compared with rrn operons

Abstract: Among the adhesin-encoding virulence operons associated with uropathogenic Escherichia coli, only pap (pyelonephritis-associated pilus)-related gene clusters typically exhibit variation in their structure and chromosomal copy number. To access further such variability, we compared pap restriction fragment length polymorphisms (RFLPs) with those detected among rRNA (rrn) operons, which encode an essential host function unrelated to virulence. To place such findings in a phylogenetic perspective, the E. coli iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 36 publications
(67 reference statements)
7
40
0
Order By: Relevance
“…Furthermore, sfa-positive strains of Maslow et al belong only to cluster III, and we have shown in this work and also previously (5) that sfa/foc operons are found only in the phylogenetic B2 group. Similarly, EcoRI rrn RFLPs and hly operon data presented by Arthur et al (1), when studying uropathogenic isolates, allows the conclusion that their group IV, which encompasses the majority of the strains, corresponds to phylogenetic B2 group strains. According to the common O18:K1:H7 strains studied by Selander et al (38) and Bingen et al (5) and to the virulence determinant distribution, most of the neonatal meningitis strains of group 1 of Selander et al correspond to phylogenetic B2 strains.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, sfa-positive strains of Maslow et al belong only to cluster III, and we have shown in this work and also previously (5) that sfa/foc operons are found only in the phylogenetic B2 group. Similarly, EcoRI rrn RFLPs and hly operon data presented by Arthur et al (1), when studying uropathogenic isolates, allows the conclusion that their group IV, which encompasses the majority of the strains, corresponds to phylogenetic B2 group strains. According to the common O18:K1:H7 strains studied by Selander et al (38) and Bingen et al (5) and to the virulence determinant distribution, most of the neonatal meningitis strains of group 1 of Selander et al correspond to phylogenetic B2 strains.…”
Section: Discussionmentioning
confidence: 87%
“…The barrier between commensalism and virulence results from a complex balance between the status of the host and the presence and expression of virulence factors in the bacteria. The genetic structure of E. coli can be considered clonal (37), and, indeed, various intestinal (41) or extraintestinal (1,26,38) E. coli infections have been linked to specific clones or groups of related clones. In several cases, pathogenicity has been correlated with the presence of genes encoding virulence factors organized on large blocks, called pathogenicity islands.…”
mentioning
confidence: 99%
“…An exam-ination of a larger number of strains from various sources will be necessary to establish whether human isolates may have greater genetic diversity than nonhuman Actinomyces strains. Substantial heterogeneity in the chromosomal DNA related to the pyelonephritis-associated pili (pap) among E. coli strains from different sources has been observed (1,32).…”
Section: Resultsmentioning
confidence: 99%
“…39). In addition, the shuffling by intra-or interspecies horizontal transfer has been found in the E. coli pap pilin (1,34), Haemophilus influenzae capsule (15), Neisseria and Streptococcus species penicillin-binding proteins (4,20,41), Salmonella 0 antigen (37), E. coli 0 antigen (18), Vibrio cholerae 0139 0 antigen (2) and Salmonella enterica flagellin (16). In Streptococcus pyogenes, recombination events have been found in the genes encoding exotoxin A (speA) (29), exotoxin B (speB) (12), exotoxin C (speC) (11), M-protein (43), M-like proteins (44) and streptokinase (10).…”
Section: Discussionmentioning
confidence: 99%